1987
DOI: 10.1111/j.2042-7158.1987.tb03129.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective agonists and antagonists for 5-hydroxytryptamine receptor subtypes, and interactions with yohimbine and FG 7142 using the elevated plus-maze test in the rat

Abstract: The effects of some 5-HT receptor ligands were investigated on measures of anxiety in an elevated plus-maze test in the rat. Quipazine (2 and 4 mg kg-1), a non-specific 5-HT agonist and ritanserin (0.25-10 mg kg-1), a 5-HT2 receptor antagonist displayed anxiogenic profiles by reducing both of the measures of anxiety used in this test. Two 5-HT1A receptor ligands, buspirone (4 and 8 mg kg-1) and ipsapirone (2.5-10 mg kg-1) and the 5-HT1 agonist, RU 24969 (0.1875-1.5 mg kg-1) significantly reduced only the perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(35 citation statements)
references
References 58 publications
2
33
0
Order By: Relevance
“…Using the in vivo microdialysis technique, the present study has demonstrated that the systemic administration of the M2-adrenoceptor antagonist, yohimbine, having anxiogenic properties in animal models of anxiety and man (Charney et al, 1983;1992;Pellow et al, 1987), significantly increased the extracellular levels of 5-HT in the frontal cortex of the freely-moving rat. Yohimbine also caused a slight but significant reduction in the frontal cortical dialysate 5-HIAA levels.…”
Section: Discussionmentioning
confidence: 96%
“…Using the in vivo microdialysis technique, the present study has demonstrated that the systemic administration of the M2-adrenoceptor antagonist, yohimbine, having anxiogenic properties in animal models of anxiety and man (Charney et al, 1983;1992;Pellow et al, 1987), significantly increased the extracellular levels of 5-HT in the frontal cortex of the freely-moving rat. Yohimbine also caused a slight but significant reduction in the frontal cortical dialysate 5-HIAA levels.…”
Section: Discussionmentioning
confidence: 96%
“…However, in previous studies with rats, the center-avoiding behavior induced by MDMA was not interpreted as evidence of increased anxiety, because familiarization with the testing environment fails to change the pattern of locomotor activity (Callaway et al 1991). On the other hand, 5-HT 1B agonists have been shown to increase anxiety in rodents (Pellow et al 1987). Without testing the effect of MDMA on a more direct measure of anxiety, such as ultrasonic vocalization in pups or elevated plus-maze behavior, it is difficult to tell whether the center-avoiding behavior seen in WT, but not KO, mice reflects the 5-HT 1B receptor's role in anxiety or its characteristic influence on the pattern of locomotor activation.…”
Section: Discussionmentioning
confidence: 99%
“…Various agonists that exhibit a certain selectivity for 5-HT 1ll receptors, such as RU 24969, TFMPP and eltoprazine, show anxiogenic-like activity in animal models such as the shock probe conflict procedure (MEER! and COLPAERT 1986), the social interaction test and the elevated plus-maze test both in rats (PELLOW et al 1987) and in mice (BENJAMIN et al 1990;RODGERS et aL 1992), although results in conflict tests in rodents are more variable (DEACON and GARDNER 1986).…”
Section: Animal Models Of Anxietymentioning
confidence: 97%